Effect of motion on the quantification accuracy of whole-body DWIBS - FAGAN, ANDREW JOHN (My University, 2012)
Background & Methods: Diffusion-weighted whole-body imaging with background body signal subtraction (DWIBS) was introduced as a qualitative approach to detecting metastases in the body. A liver-mimicking phantom with embedded tumours, which could be moved to replicate respiratory motion, was developed to assess its ability to accurately quantify ADC values. Results: Mean tumour ADC values were unaltered by the motion; however a significant (p<0.05) increase in the spread of ADC values was measured, even for relatively large tumours. Conclusions: These findings may be of significance in cancer therapy monitoring where subtle changes in ADC histograms may reveal changes in tumour heterogeneity.
PUBLISHED
Keywords: DWIBS; Quantification; ADC; Motion